Angels : who they are and how they help... what the Bible reveals - Jeremiah, David, 1941-; Jeremiah, David (New York, Multnomah, 2006)
Using Scripture to unveil the remarkable truth about angels, a senior pastor presents clear, powerful details about angels, and their role and work in the world and in people's lives.
What in the world are angels doing? -- In the presence of angels, part I -- In the presence of angels, part II -- The angels and God -- What angels are -- When angels appear -- The angels and us : how much alike? -- Angels you've heard about (and more) -- The greatest angel -- Showing us how to worship -- Showing us how to work -- Coming to carry me home -- Hell's angels -- The angels and Jesus.
Rev. ed. of: What the Bible says about angels.
Originally published: Sisters, Or. : Multnomah Publishers, 2006.
Includes bibliographical references (p. 223) and indexes.
Keywords: Angels -- Biblical teaching